2009
DOI: 10.1152/japplphysiol.91186.2008
|View full text |Cite
|
Sign up to set email alerts
|

Cessation of daily wheel running differentially alters fat oxidation capacity in liver, muscle, and adipose tissue

Abstract: Physical inactivity is associated with the increased risk of developing chronic metabolic diseases. To understand early alterations caused by physical inactivity, we utilize an animal model in which rats are transitioned from daily voluntary wheel running to a sedentary condition. In the hours and days following this transition, adipose tissue mass rapidly increases, due in part to increased lipogenesis. However, whether a concurrent decrease in fatty acid oxidative capacity (FAO) in skeletal muscle, liver, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(84 citation statements)
references
References 48 publications
6
74
1
3
Order By: Relevance
“…(Brownlow et al 1996.) However, as several recent studies have demonstrated, many pathological metabolic events associated with chronic diseases may be prevented or delayed when physical activity is commenced (Linden et al 2013;Rector et al 2010;Laye 2009;Lakka & Laaksonen 2007). Physical activity is defined by the Centers for Disease Control and Prevention (CDC) as "any bodily movement produced by the contraction of skeletal muscle that increases energy expenditure above a basal level.…”
Section: Physical Activitymentioning
confidence: 99%
“…(Brownlow et al 1996.) However, as several recent studies have demonstrated, many pathological metabolic events associated with chronic diseases may be prevented or delayed when physical activity is commenced (Linden et al 2013;Rector et al 2010;Laye 2009;Lakka & Laaksonen 2007). Physical activity is defined by the Centers for Disease Control and Prevention (CDC) as "any bodily movement produced by the contraction of skeletal muscle that increases energy expenditure above a basal level.…”
Section: Physical Activitymentioning
confidence: 99%
“…Booth and colleagues (27)(28)(29)(30)38) published a series of "wheel lock" studies to determine the mechanisms by which acute inactivity leads to metabolic dysfunction. Rats provided with voluntarily running wheels (VWR) in their cages will voluntarily run during the dark cycle.…”
Section: Wheel Lock Studies In Rodentsmentioning
confidence: 99%
“…Running volumes can vary from ϳ1 up to 20 km over a 12-h dark cycle period but are typically consistent within experiments. In addition, the mitochondrial adaptations in skeletal muscle after VWR (29,39) are usually very modest and pale in comparison to what is measured in rats forced to run on treadmills (11). Therefore, it could be argued that VWR in rats is analogous to higher daily ambulatory activity in humans, while treadmill running in rats would mimic programmed endurance exercise in humans.…”
Section: Wheel Lock Studies In Rodentsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence from rodent (7,18,27) and human (25) studies that cessation of physical activity for 7-10 days is sufficient to increase visceral adiposity. It is not uncommon for humans to transition repetitively from periods of high physical activity to periods of inactivity and vice versa over their lifespan.…”
mentioning
confidence: 99%